A Study Case of Analysis and Needs of Distance Learning at Mandailing Natal District Senior High Schools during the Covid-19 Pandemic - Sulhan Hamid H Lubis; M. Joharis Lubis; Lidya Ardiyan; Rusdiman AB (Budapest International Research and Critics University, 2021)
This study discusses learning which was originally carried face-to-face but then became distance learning in a high school in Mandailing Natal Regency during the COVID-19 pandemic. This study analyzes the learning and the needs during distance learning. This qualitative data research employed non-probability sampling technique by means of purposive sampling so that the sample in this study was 50 teachers and 100 students in different schools. The data collection used was survey method. The data were analyzed by descriptive statistics. The main findings show that Distance Learning can be implemented well. The findings in the field are that most of all schools implement distance learning from home except for a small number. Teachers experience major obstacles in implementing learning from home. There are still a few teachers who do interactive learning with students but have used various social media tools to communicate with students. There are still many teachers who teach curriculum completeness. The duration of the learning time is significantly reduced. Students also experience problems during distance learning, such as limited facilities to support skills in using digital devices, and decreased learning motivation and teachers have not maximized the use of online learning platforms.